A study of COD and ammonia removal by adsorbent (activated carbon, zeolite and clay) from landfill leachate - Ridzuan, Mohd Baharudin; Daud, Zuikarnain; Ahmad, Z. (UTHM Publisher, 2017)
The use of zeolite, clay and activated carbon media in wastewater treatment and leaching has become increasingly popular today as it has the potential to improve water quality, as well as low maintenance and operating costs. This study aims to determine the optimum mix media of the adsorption agent and determine the mineral content in the adsorption agent using XRF and SEM, in addition, determine the cation exchange capacity (CEC) value of the adsorbent and determine the kinetic model of adsorbent material on the removal of COD and Ammonia. The leachate sample was taken from the CEP landfill, Machap, Johor, Malaysia. Mixed media design of adsorbent material is in percentages of 0%, 40%, 60%, 80% and 100%. Each set will be tested on touch time for 2 hours, 4 hours and 8 hours. The parameters to be performed are chemical oxygen demand (COD), turbidity, ammonia nitrogen and pH. The results showed that the optimum touch time for the removal percentage was at 8 hours of touch time. On the first backwash method and the second backwash find the optimum touch time at 4 hours of touch time. The removal rate for ammonia and chemical oxygen demand reaches the removal target of 80% removal.